Status of vaccine research and development of vaccines for HIV-1. Issue 26 (3rd June 2016) - Safrit, Jeffrey T.; Fast, Patricia E.; Gieber, Lisa; Kuipers, Hester; Dean, Hansi J.; Koff, Wayne C.
Highlights: HIV is highly variable thus requiring broad immune responses for an effective vaccine. Without correlates of protection, there is still much to learn about immunity to HIV. HIV-specific CD8 + T cells and bNAbs are both difficult to induce with vaccines. Whether DNA, protein or viral vector, vaccine designs now emphasize broad coverage. Abstract: Human immunodeficiency virus (HIV) is the cause of one of the most lethal pandemics in human history, although in recent years access to highly effective anti-retroviral therapy has provided new hope worldwide. Transmission of HIV by sexual contact, childbirth and injection drug use has been reduced, but 2 million are newly infected each year, and much of the transmission is from people who do not know their status. In addition to known methods, a preventive vaccine is needed to end the pandemic. The extraordinary mutability and genetic diversity of HIV is an enormous challenge, but vaccines are being designed for broad coverage. Computer-aided design of mosaic immunogens, incorporating many epitopes from the entire genome or from conserved regions aim to induce CD8+ T cells to kill virus-infected cells or inhibit virus replication, while trimeric envelope proteins or synthetic mimics aim to induce broadly reactive neutralizing antibodies similar to those cloned from some infected patients. Induction of more potent and durable responses may require new adjuvants or replicating chimeric vectors chimeras that bear HIV genes. Passive or genetic delivery of broadly neutralizing antibodies may provide broad protection and/or lead to insights for vaccine designers. Proof-of-concept trials in non-human primates and in one human efficacy trial have provided scientific clues for a vaccine that could provide broad and durable protection against HIV. The use of vaccines to destroy HIV reservoirs as part of therapy or cure is now also being explored.